Unmet need for healthcare in the Russian Federation: subnational retrospective modelling analysis (2014-2018) - Elias Mossialos; Vladimir M Shkolnikov; Zlatko Nikoloski; Aparnaa Somanathan; Igor Sheiman (BMJ Publishing Group, 2024)
Introduction Unmet need for healthcare is a proxy indicator used to assess the performance of healthcare systems throughout the world. While the Russian Federation is committed to improving healthcare for its citizens, barriers to access remain.Methods Using data from a region-level survey, we document and analyse the extent of the unmet need for healthcare at both national and subnational levels in the Russian Federation for the years 2014-2018. We used a panel fixed effects modelling approach to examine the link between unmet need and its correlates at the subnational level. We also used data from various sources that addressed the reasons underlying unmet need to interpret the findings from the modelling analysis.Results Approximately one-third of the Russian population (34.7% in 2018) reported that healthcare was not received when it was needed with little change observed between 2014 and 2018. We observed significant variation across the various regions in Russia. The prevalence of unmet need was substantially higher in the regions of the Volga, Siberia and Far East Federal Districts. Our analysis revealed that the density of hospital beds and economic development across regions were correlated with the prevalence of unmet need. Dissatisfaction with healthcare services, perceived lack of effective treatments and financial constraints were the main reasons offered for forgoing healthcare when needed.Conclusions An unanticipated positive link between unmet need and hospital bed density might be attributed to the low accessibility and quality of primary healthcare. High demand and supply of inpatient care do not compensate for the structural imbalances of the current healthcare model. Strengthening and improving the quality of primary care might significantly reduce the prevalence of unmet need.